PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT OF BASIL LEAVES (Ocimum sanctum L.) AGAINST Propionibacterium acne BACTERIA - Didin Ahidin; Didi Rohadi; Iin Indawati; Muh Yani Zamzam; Rinto Susilo; Nurcholisah; Andriana (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Acne is a skin disease often experienced by teenagers and young adults. Basil leaves (Ocimum sanctum L.) could be used as an alternative treatment for acne. This study aimed to determine the secondary metabolite content and antibacterial activity of Ocimum sanctum ethanol extract against Propionibacterium acne. Simplicia was extracted from basil leaves by maceration with 96% ethanol solvent. The extracts were tested for parameters, phytochemical screening, and antibacterial activity using the disc diffusion method. Ocimum sanctum ethanol extract was used at concentrations of 20%, 30%, and 40%. Ocimum sanctum ethanol extract has a brownish-black color with a distinctive aromatic aroma and a bitter, slightly sour taste, with a moisture content of 5.6%, ash content of 7.71%, and drying shrinkage of 7.1%. Ocimum sanctum ethanol extract contains flavonoids, tannins, steroids, and saponins. Antibacterial activity of clindamycin 0.01% and Ocimum sanctum ethanol extract concentration of 20%, 30%, and 40% could inhibit Propionibacterium acne bacteria as much as 11.95 mm, 4.47 mm, 4.91 mm, and 6.30 mm. The antibacterial activity of the Ocimum sanctum ethanol extract was 20%. The 30% and 40% treatments differed significantly from the positive controls. The ethanol extract of basil leaves has antibacterial activity against Propionibacterium acne bacteria with the best antibacterial activity at a concentration of 40% as much as 6.30 mm. Keywords: Basil leaf (Ocimum sanctum L.), phytochemical screening, antibacterial activity